PENGEMBANGAN MODEL 4CM (COOL-COOPERATIVE -CRITICAL- CREATIVE-MEANINGFUL) LEARNING DALAM BLENDED LEARNING - Ratni Purwasih; Eva Dwi Minarti (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This study aims to develop a 3CM learning model in blended learning. The method used in this research is R&D with the Plomp model. The Plomp model consists of preliminary research (preliminary research; 2) the design phase; 3) realization/construction phase; 4) test, evaluation and revision phases; and 5) implementation phase. The data collection technique uses a validation sheet to measure the feasibility of the 3CM learning model in blended learning. conducted by 3 experts and a practical sheet to measure the practicality of the 4CM learning model in blended learning conducted by 3 teacher practitioners. The results of the study are that the 3CM learning model developed has met the valid criteria, is very practical and effective. The implication of this research is that the 4CM learning model developed can be used by teachers on blended learning prism material